Java servlet and JSP cookbook - Perry, Bruce W. (O'Reilly, 2004)
With literally hundreds of examples and thousands of lines of code, the Java Servlet and JSP Cookbook yields tips and techniques that any Java web developer who uses JavaServer Pages or servlets will use every day, along with full-fledged solutions to significant web application development problems that developers can insert directly into their own applications. Java Servlet and JSP Cookbook presents real-world problems, and provides concise, practical solutions to each. Finding even one tested code ""recipe"" that solves a gnarly problem in this comprehensive coll